A COMPARATIVE STUDY OF CLONIDINE VERSUS FENTANYL FOR INTRAOPERATIVE HEMODYNAMIC STABILITY IN PATIENTS UNDERGOING LAPAROSCOPIC CHOLECYSTECTOMY UNDER GENERAL ANESTHESIA: RANDOMIZED, DOUBLE-BLIND, INTERVENTIONAL STUDY - GARG, PAVAN KUMAR; JOSHI, NAND KISHORE; CHAUHAN, SUNIL (International Journal of Current Pharmaceutical Research, 2024)
Objective: Laparoscopic cholecystectomy, though advantageous over traditional surgery, presents hemodynamic challenges due to pneumoperitoneum, systemic CO2 absorption, and patient positioning. Clonidine and Fentanyl are evaluated for their effectiveness in maintaining intraoperative hemodynamic stability, considering their different pharmacological actions. Methods: This randomized, double-blind interventional study involved 72 patients undergoing elective laparoscopic cholecystectomy under general anesthesia. Participants were allocated into two groups, receiving either IV Clonidine or IV Fentanyl. Hemodynamic parameters, including heart rate and blood pressure, were monitored and compared. Results: Clonidine demonstrated superior control over heart rate and blood pressure compared to Fentanyl, with statistically significant differences observed in the intraoperative period and post-intubation, indicating enhanced hemodynamic stability. Conclusion: Clonidine is more effective than Fentanyl in maintaining intraoperative hemodynamic stability in patients undergoing laparoscopic cholecystectomy. This suggests a potential preference for Clonidine as a premedicant in such surgical procedures, highlighting the need for tailored anesthetic techniques.